Nation-Building in Madagascar: The Place and Role of Fihavanana in the Reconciliation Process. Issue 2 (3rd July 2022) - Lekaba, Frank
Abstract: This article argues that SADC (the Southern African Development Community) and local role players in Madagascar missed the opportunity to use the notion of fihavanana in the country's reconciliation process. Literature on Madagascar's post-2009 instability predominantly deals with the successes and failures of SADC's mediation. Less focus is placed on how fihavanana can serve as a political tool in addressing issues of nation-building. This article employs a critical literature review and a discussion of the African philosophy of fihavanana to analyse the utility of fihavanana in Madagascar's reconciliation and mediation processes. Madagascar is a country with vast and varying ethnic groups, categorised as the Côtiers (coastal ethnic groups) and the Merina. The island has a history of ethnic divisions and polarisation, exacerbated by the consolidation of the Merina kingdom and French colonisation. The reconciliation process is analysed in the broader context of nation-building. The aim of this article is to contribute an analysis of how endogenous concepts and principles could contribute to the body of knowledge on peacebuilding from below.